Territorial Re-existences of Indigenous Movements in the Andean-Amazon Region - Lopez-Flores, Pabel-Camilo (ANDULI, Revista Andaluza de Ciencias Sociales, 2024)
Movements by indigenous peoples against neoliberal extractivist processes in Latin America have traditionally employed strategies focused on territorial recognition of their identity and culture. The issue under investigation is the recent resurgence of post-extractivist territorial-based social movements that are using strategies based on innovative economic models and creative development. The objective is to study these territorial social movements and socio-ecological conflicts by analyzing cases in the Andean-Amazonian region in Bolivia and Colombia. The methodology is qualitative and ethnographic, based on interviews and documentary analysis. In the case of the Rositas River in Bolivia, indigenous communities and producers have organized to oppose the construction of a dam and hydroelectric project. In the Colombian region of Cauca, the dispute is over 20,000 hectares of sugarcane monoculture where the local community is fighting to grow corn, beans and yucca. The common characteristics of these movements are ecofeminist involvement, autonomous forms of collective action and political experimentation, new languages, and patterns of struggle and mobilization including the deployment of international alliances.